PROTOCOL: Hate online and in traditional media: A systematic review of the evidence for associations or impacts on individuals, audiences, and communities - Hassan, Ghayda; Rabah, Jihan; Madriaza, Pablo; Brouillette‐Alarie, Sebastien; Borokhovski, Eugene; Pickup, David; Varela, Wynnpaul; Girard, Melina; Durocher‐Costa, Loïc; Danis, Emmanuel (Campbell systematic review, 2022)
This is the protocol for a Campbell systematic review: The objectives are as follows: (1) to critically and systematically synthesize the empirical evidence on the effects or impacts of exposure to or consumption, active search, or promotion of hate content online or in traditional media; (2) to describe how the characteristics of hate (e.g., type of content, ideologies, severity, type of platform) impact the documented effects; (3) to collect and identify the role of contextual variables (e.g., individual traits, age, gender, socio‐economic background) on the documented effects; (4) to collect and produce a meaningful classification of outcomes; and (5) to identify gaps and limitations in the research and related policy documents.